Significance of Viva Exams for English Language Learning (ELL) in Pakistan - Mahwish Farooq (Linguistics and Literature Review, 2017)
This study deals with the reformation for English Language Learning (ELL) by considering the need and importance of viva exam. Therefore, it has been conducted in ELL classes of Public Sector University in Pakistan. English language teaching is a crucial issue therefore different methods have been used to teach and evaluate the performance of learners. But the most important element, viva is being ignored in our Public Sector Universities. Strategically, language teaching is a quite different subject but is being taught similar to other subjects which adds more difficulty. Actually, English must be considered a practical subject where learners have to participate in different experimental tasks. It is an observational study where a checklist has prepared by the researcher for collecting objective information. So, it is designed with sixty learners, divided in 3 groups of 20 participants in each. Two groups have been taught by the same teacher, having same curriculum and methodology. Group 1 is informed about the viva in qualifying exams therefore actively participated in spoken activities. But Group 2 is kept uninformed till the end of the course so tries to avoid participation. Group 3 has been asked to give opinion about the research by answering questionnaire. Then, the data interpretation and results concluded that emergence of viva exams and exam fear fact are the important elements to achieve English language proficiency.